Fungsi Ilmu Hadits dalam Memelihara Sunnah Nabi dan Penerapannya secara Praktis - Madsuri (Bayani, 2025)
that plays a role as the main fortress in maintaining the authenticity of the words and behavior of the Prophet Muhammad ?. This article aims to comprehensively examine the role of hadith science as a verification methodology for matan and sanad, while analyzing its contribution in forming Islamic law and building a Muslim civilization based on authentic sources. This study uses a qualitative approach with a content analysis method for scientific literature. The results of the study show that hadith science not only functions as a tool for text criticism (?????? ????????), but also as a unique system for guarding the transmission of knowledge (?????? ????????) in the history of human civilization.